OP16 Endoscopic and clinical outcomes of upadacitinib in patients with moderately to severely active Crohn's disease by number and type of prior biologics. (30th January 2023) - Peyrin-Biroulet, L; Parkes, G; Rodríguez, C; Siffledeen, J; Wright, J; Broide, E; Ford, S; Lacerda, A P; Oomen, J; Garrison, A; Berg, S; Rubin, D T
Abstract: Background: Biologic therapies are used to treat moderate-to-severe Crohn's Disease (CD), but many patients eventually lose response to them. With new potential therapies for CD, understanding their efficacy after patients undergo biologic treatment is important for clinical decision-making. This post hoc analysis assessed the outcomes of upadacitinib (UPA), an oral selective Janus kinase inhibitor, in patients with CD who had failed a biologic, by the number and type of prior biologic therapies. Methods: In the 2 induction studies, U-EXCEL (NCT03345849) and U-EXCEED (NCT03345836), patients with moderate-to-severe CD received oral UPA 45 mg once daily (QD) therapy or placebo (PBO) for 12 weeks. Patients achieving clinical response to UPA induction were re-randomised in the maintenance study, U-ENDURE (NCT03345823), to receive UPA 15 mg QD, UPA 30 mg QD, or PBO for 52 weeks. This analysis assessed clinical, endoscopic, and safety outcomes in patients with inadequate response or intolerance to biologic therapy by number and type of biologics failed. Data from the U-EXCEL and U-EXCEED studies were pooled. Results: At baseline, patient (n=733) characteristics were similar for UPA vs PBO within each subgroup by number of prior biologics (1, n=279; 2, n=223; >2, n=231); patients who received ≥ 2 prior biologics had longer disease duration (median, years: 1, 6.2; 2, 9.4; >2, 12.9) and were more likely to have used steroids (1, 27.7%; 2, 40.4%; >2, 45.0%). Across subgroups, greater proportions of patients receiving UPA vs PBO achieved clinical remission (Figure 1) and endoscopic response and remission (Figure 2) at week 12 of induction and week 52 of maintenance; response rates were generally higher for patients who had failed fewer biologics. When analyzed by type of prior biologic (tumor necrosis factor inhibitor [yes/no], n=704/29; ustekinumab [yes/no], n=272/461; vedolizumab or natalizumab [yes/no], n=220/513), the proportion of patients achieving clinical and endoscopic outcomes was slightly higher for those without prior exposure to each biologic. Adverse events (AEs) occurred at numerically higher rates for patients who had failed multiple biologics in the induction and maintenance studies across both PBO and UPA treatment arms. AEs of special interest occurred at similar rates across subgroups. No non-melanoma skin cancers, major adverse cardiovascular events, or venous thromboembolic events were reported. Conclusion: Clinical and endoscopic improvements were observed with UPA induction and maintenance therapy in patients with moderate-to-severe CD, regardless of number and type of prior biologics failed; greater benefits and fewer AEs were observed in patients who failed fewer biologic therapies.